2021
DOI: 10.1002/ange.202109802
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Isomerism on Radioluminescence of Purely Organic Phosphorescence Scintillators

Abstract: There are few reports about purely organic phosphorescence scintillators, and the relationship between molecular structures and radioluminescence in organic scintillators is still unclear. Here, we presented isomerism strategy to study the effect of molecular structures on radioluminescence. The isomers can achieve phosphorescence efficiency of up to 22.8 % by ultraviolet irradiation. Under X-ray irradiation, both m-BA and p-BA show excellent radioluminescence, while o-BA has almost no radioluminescence. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…More importantly, the X-ray imaging screens created using TADF-Br chromophore exhibited a relative light yield of approximately 20,000 photons/MeV, which is 5 times higher than that of the best TADF scintillator reported recently (the highest relative light yield among reported TADF scintillators is 3700 photons/MeV 15 according to the calculation method provided in this article). 15,19,32,33 In addition, the detection limit of 64.5 nGy s -1 obtained for the TADF-Br film is several times lower than the standard dosage for X-ray diagnostics (5.5 μGy s -1 ) 1 . Moreover, a high X-ray imaging resolution of 18.3 lp mm -1 can be achieved, exceeding all the reported organic and most conventional inorganic scintillators.…”
Section: Introductionmentioning
confidence: 80%
“…More importantly, the X-ray imaging screens created using TADF-Br chromophore exhibited a relative light yield of approximately 20,000 photons/MeV, which is 5 times higher than that of the best TADF scintillator reported recently (the highest relative light yield among reported TADF scintillators is 3700 photons/MeV 15 according to the calculation method provided in this article). 15,19,32,33 In addition, the detection limit of 64.5 nGy s -1 obtained for the TADF-Br film is several times lower than the standard dosage for X-ray diagnostics (5.5 μGy s -1 ) 1 . Moreover, a high X-ray imaging resolution of 18.3 lp mm -1 can be achieved, exceeding all the reported organic and most conventional inorganic scintillators.…”
Section: Introductionmentioning
confidence: 80%
“…[6] However, acquirement of purely organic phosphorescence with a long lifetime faces a great challenge because of the inherently weak spinorbital coupling (SOC) or fast intersystem crossing (ISC) process and multiple deactivation pathways of organic molecules, all of which will shorten the phosphorescence lifetime (microsecond-or millisecond-level), and even cause the lack of phosphorescence. [7] To achieve long-lived and high-performance purely organic phosphorescence, lots of effort have gone into the design and synthesis, including crystallization, [8][9][10][11] embedding chromophores into the matrix, [12][13][14] polymerization, [15][16][17] deuterium substitution, [18] supramolecular host-guest interaction, [2e, 19, 20] and so on, [21,22] most of which are mainly based on the principle of minimizing nonradiative relaxation and enhancing the ISC process of excitons from the lowest singlet excited state (S 1 ) to the triplet manifold (T n ). Although there are numerous outstanding works, second-level phosphorescence emission is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that radiative decay was highly dependent on material conductivity caused by different molecular packing modes. 8 Ma et al proposed the conversion feature of the organic singlecomponent small molecule 1,2-bis(4-alkoxyphenyl)ethane-1,2dione (N-BOX), which could switch between high-efficiency blue and yellow RTP emissions. In particular, the RTP quantum yield of 7-BOX could reach 68.4% by grinding or thermal annealing.…”
Section: Introductionmentioning
confidence: 99%